Locus of Control Mediation: Effect of financial Knowledge and financial Attitude on Financial Management Behavior - Muntafiah Muntafiah; Muhammad Rexsa Assyarofi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to determine whether there is an influence of financial knowledge and financial attitude on financial management behavior through locus of control. The population in this study consists of students in the Solo Raya area, with a sample size of 250 respondents. This research employs a quantitative approach using SEM-SmartPLS as the analysis tool. The results of this study indicate that (1) there is an influence of financial knowledge on financial management behavior, (2) there is an influence of financial attitude on financial management behavior, (3) there is an influence of locus of control on financial management behavior, (4) there is no influence of financial knowledge on locus of control, (5) there is an influence of financial attitude on locus of control, (6) there is no influence of financial knowledge on financial management behavior through locus of control, and (7) there is an influence of financial attitude on financial management behavior through locus of control.